2010
DOI: 10.2176/nmc.50.1070
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Gabapentin for Radiculopathy Caused by Lumbar Spinal Stenosis and Lumbar Disk Hernia

Abstract: The efficacy of gabapentin monotherapy was investigated against both acute or chronic radicular pain caused by lumbar disk hernia (LDH) or lumbar spinal stenosis (LSS). Seventy-eight patients with radicular pain, 10 males and 68 females aged 23 to 76 years (mean 49.4 years), caused by LSS in 45 patients or LDH in 33 patients were treated with oral administration of gabapentin and were followed up for 3 months. The evaluation included neurological examination, Odom's criteria, visual analog pain scale (VAS), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
2
12
2
Order By: Relevance
“…Identification of neuropathic components is critical to the medical treatment of degenerative spinal disease because the therapeutic approach for these patients should be different from that for patients with only nociceptive pain. 2 23 24 The present study showed that the Korean version of DN4 has excellent psychometric properties: we confirmed its high discriminative ability in patients with neuropathic component pain or nociceptive pain, with an AUC score of 0.953, a sensitivity of 100% and 87.1%, and a specificity of 88.2% and 94.1% at the cutoff values of 3/10 and 4/10, respectively. This finding is consistent with previous studies with other languages, 11 12 16 where the cutoff value for the DN4 questionnaire in most of them was established at 4/10.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Identification of neuropathic components is critical to the medical treatment of degenerative spinal disease because the therapeutic approach for these patients should be different from that for patients with only nociceptive pain. 2 23 24 The present study showed that the Korean version of DN4 has excellent psychometric properties: we confirmed its high discriminative ability in patients with neuropathic component pain or nociceptive pain, with an AUC score of 0.953, a sensitivity of 100% and 87.1%, and a specificity of 88.2% and 94.1% at the cutoff values of 3/10 and 4/10, respectively. This finding is consistent with previous studies with other languages, 11 12 16 where the cutoff value for the DN4 questionnaire in most of them was established at 4/10.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies have consistently emphasized the identification and treatment of neuropathic pain component for the treatment of degenerative spinal disease. 2 23 24 25 26 In this perspective, the present study also highlights possible or probable neuropathic pain of degenerative spinal disease. Second, it has not yet been determined whether the DN4 questionnaire can be used to detect possible or probable neuropathic pain.…”
Section: Discussionmentioning
confidence: 57%
“…In patients treated with gabapentin, the mean pain score reduced significantly to 3.89 from 8.27. This finding was similar to the study conducted by Kasimcan et al 34 Pain reduction in patients treated with pregabalin was 52.63%, and with gabapentin it was 52.96% at the end of 12 weeks. Hence, pregabalin showed comparable pain reduction as compare to gabapentin [52.63% vs. 52.96%] at the end of 12 weeks study.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study showed that gabapentin could be an option in the conservative management of acute or chronic radicular pain caused by lumbar disc herniation or lumbar spinal stenosis 87. In another study, Ucak et al88 compared gabapentin with placebo and showed that gabapentin significantly reduced the intensity of pain and tramadol consumption relative to placebo when used in the early postoperative period after coronary artery bypass graft surgery.…”
Section: Nonopioid Medications Used As Analgesicsmentioning
confidence: 99%